PENGARUH EFFLEURAGE MASSAGE TERHADAP NYERI PERSALINAN KALA I FASE AKTIF - Nelly Karlinah; Cecen Suci Hakameri (Jurnal Online Keperawatan Indonesia, 2022)
Labor pain is something that is commonly felt by pregnant women just before the birth process. But if it is not treated with proper pain management, it will cause problems, one of which is the emergence of anxiety, stress, and feelings of worry. For this reason, it is necessary to have labor pain management, one of which is with Effleurage Massage. The study aimed to determine the effect of Effleurage Massage on Labor Pain during the Active Phase I in the Independent Midwife Practice (PMB) in Hasna Dewi, Pekanbaru City. This type of research is pre-experimental with two group pretest and posttest designs. The time of research was carried out in August-November 2022. The sample in this study was 10 respondents using a total sampling technique. The research instrument used a Numerical Rating Scale (NRS) questionnaire. Univariate and bivariate data analysis. Univariate results showed pain before being given effleurage massage moderate pain with a percentage of 90.0%. pain after being given effleurage massage pain decreased to mild pain with a percentage of 90.0%. The results of the Wilcoxon Rank Test showed that there was an effect of effleurage massage on pain in the active phase of the first stage of labor with a P value of 0.002 <0.05. The conclusion is that there is an effect of effleurage massage on pain in the first active phase of labor. It is recommended for health workers to be able to use effleurage massage to reduce pain in the active phase of labor during the first stage.